The National Land Code Form 16D v 16E: Jacob v. Overseas-Chinese Banking Corporation - Lim, M.H.K (Journal of Malaysian and Comparative Law, 1974)
The National Land Code Form 16D v 16E: Jacob v. Overseas-Chinese Banking Corporation